Structure of Pinus nigra Arn. populations in Bulgaria revealed by chloroplast microsatellites and terpenes analysis: Provenance tests - Naydenov, Krassimir D.; Tremblay, Francine M.; Fenton, Nicole J.; Alexandrov, Alexander (Biochemical systematics and ecology, 2006)
Pinus nigra is a forest and low elevation mountain species found around the Mediterranean Sea that has had its distribution reduced and fragmented by anthropogenic disturbance. Due to commercial interest it is currently being replanted, however, the genetic structure of populations is little known and current planting strategies could threaten its genetic diversity. In the present study we investigated the genetic structure and genetic diversity of P. nigra populations in Bulgaria using chloroplast microsatellite markers and terpene analysis. Nine provenances were chosen throughout the species' range in Bulgaria. Following DNA extraction, chloroplast microsatellite (cpSSR) loci were surveyed using three primer pairs. Between 5 and 9 size variants were identified at each locus. A total of 22 size variants at the 3 loci were identified, that were combined in 68 different haplotypes, of which 7 represent 39.81% of the genetic structure. AMOVA analysis revealed that 6.06% of the variation was found among populations, while 93.94% was expressed within populations. The cpSSR analysis divided European Black pine populations into four groups, the first represented by populations located the eastern Rhodopes, Sr. Gora and St. Planina mountains, while the second group is primarily located in the Phodopes and Slavianca mountains. The populations from Pirin and Osogovo mountains show different genetic patterns. Terpene analysis revealed that most of the monoterpene pool in P. nigra was accounted for by α-pinene followed by β-pinene. The presence of four distinct terpene groups is not consistent with physical distances between populations, and a similar non-significant correlation between genetic distance determined by chloroplast microsatellites analysis and chemotype distance (determined by terpenes) was observed. Our results suggest that the structural pattern of genetic diversity of cpDNA in European Black pine populations is the consequence of historical biogeographic processes.